Enterprise-wide simultaneous deployment of ambient scribe technology: lessons learned from an academic health system - Wright, Aileen P; Nall, Carolynn K; Franklin, Jacob J H; Horst, Sara N; Kumah-Crystal, Yaa A; Wright, Adam T; Mize, Dara E (Journal of the American Medical Informatics Association : JAMIA, 2025)
To report on the feasibility of a simultaneous, enterprise-wide deployment of EHR-integrated ambient scribe technology across a large academic health system. On January 15, 2025, ambient scribing was made available to over 2400 ambulatory and emergency department clinicians. We tracked utilization rates, technical support needs, and user feedback. By March 31, 2025, 20.1% of visit notes incorporated ambient scribing, and 1223 clinicians had used ambient scribing. Among 209 respondents (22.1% of 947 surveyed), 90.9% would be disappointed if they lost access to ambient scribing, and 84.7% reported a positive training experience. Enterprise-wide simultaneous deployment combined with a low-barrier training model enabled immediate access for clinicians and reduced administrative burden by concentrating go-live efforts. Support needs were manageable. Simultaneous enterprise-wide deployment of ambient scribing was feasible and provided immediate access for clinicians.